A Novel Technique for Resolver-to-Digital Conversion Using Principal Frequency Component S-Transform. (11th December 2019) - He, Like; Yi, Jiliang
Abstract : A novel technique for resolver-to-digital conversion (RDC) using principal frequency component S-transform (PFCST) is proposed in this paper. First, the mode envelope of two output signals of the resolver is extracted by PFCST. The envelope extracted by PFCST maintains the same time resolution as the original signal because it performs time-frequency conversion for each sampling point. Then, the quadrant of the resolver is determined by the judgment rule formed by the polarity of the optimum nonzero region of the signals, and the quadrant information is used to correct the arctangent to obtain the accurate rotor position. Finally, the simulations prove that the maximum angle error of the resolver estimated by this method occurs at the quadrant junction but does not exceed one deg., and the experiments are used to verify the effectiveness of the proposed method.